Senam Hamil dengan Kualitas Tidur Ibu Hamil di UPT Puskesmas Sooko Kabupaten Mojokerto - Zulfa Rufaida; Sri Wardini Puji Lestari; Ika Yuni Susanti (Jurnal Kesehatan Masyarakat Mulawarman (JKMM), 2021)
Pregnancy often causes disturbances in sleep patterns, both in terms of the duration and quality of sleep, this is caused by psychological and physical changes in pregnant women. The purpose of this study was to determine the relationship between pregnancy exercise and the quality of sleep of pregnant women at the UPT Puskesmas Sooko, Mojokerto Regency.The type of research used in this research is correlational. using cross sectional design. Independent variables of pregnancy exercise and the dependent variable on the quality of sleep of pregnant women. The sampling technique used was simple random sampling with a population of 32 respondents and a sample size of 30 respondents. Data were collected during February - March 2020, the instruments used were interviews and questionnaires. The analysis technique used the chi square test.The results of this study were 22 pregnant women who did not exercise (73.3%), 13 people who experienced poor sleep quality (43.7%)Test results The results of the Fisher's exact statistical test showed ρ = 0.04 and α = 0.05, it was stated ρ <α, so H1 was accepted, meaning that there was a relationship between pregnancy exercise and the quality of sleep of pregnant women.As it is known that pregnancy exercise affects the quality of sleep for pregnant women, it is necessary to improve services during ANC regarding pregnancy exercise services to improve the quality of sleep for pregnant women.